Improved services traceability and management of a food value chain using block-chain network: a case of Nigeria - Maureen Ifeanyi Akazue; Rume Elizabeth Yoro; Bridget Ogheneovo Malasowe; Obinna Nwankwo; Arnold Arnold Ojugo (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Competitive asset markets and increased globalization have continued to ripple the food value chain with complex dynamics, which has led to a range of challenges such as food safety and quality, traceability, and overall supply chain inefficiency. These have further continued to endanger the general well-being of society. With rice as a staple food in Nigeria, the rice food supply value chain consists of a series of tasks, processes, and activities that are linked together from freshly harvested products to consumer demand and supply. Study advances the SmartRice, a sensor-based block-chain framework that decentralizes as well as provides a decision-support for the food supply value chain process by first ensuring that accurate data of harvested goods are reported, and passed on to a chain. The study advances a decentralized framework to eliminate various forms of fraud rippled across the existing centralized system, minimize corruption through its sensor-based layered model as well as minimize the error in reported data along the value chain.